Efektivitas Pregnancy e-Conseling terhadap Perilaku Kesehatan Maternal Selama Masa Pandemic COVID-19 - Mira Rizkia; Halifah, Elka; Ardhia, Dara; Darmawati, Darmawati; Martina, Martina (LPPM Hang Tuah Pekanbaru, 2025)
The majority of pregnant women during the COVID-19 pandemic are reluctant to receive prenatal care for fear of being exposed to the virus, so online counseling is an alternative. This study aimed to identify the effectiveness of Pregnancy e-Counseling (PeC) on prenatal health behavior during pregnancy during the COVID-19 period. This research is quasi-experimental research with a pre-post test and control group design. The sampling technique was a simple random sampling of 94 respondents divided by 47 pregnant women in the control group and 47 in the intervention group in 6 health centers in Aceh Besar. The PeC intervention began with a Focus Group Discussion (FGD) followed by online counseling guided by a counselor and the provision of specially designed videos about the health of pregnant women during COVID-19. The instrument used was the standard Prenatal Health Behavior Scale (PHBS) questionnaire. The results showed a significant difference between prenatal health behavior before and after PeC in the intervention group with the Wilcoxon Test (p=0.000) and at the post-test between the control and intervention Mann-Whitney Test (p=0.000). Conclusion PeC is a very effective method to improve maternal health behavior during pregnancy, especially during a pandemic. So, it is highly recommended that PeC can be applied as part of a pregnancy visit to improve prenatal health.